Pustakawan Perguruan Tinggi Di Era Disrupsi: Berubah Atau Punah - Wulandini, Septi (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2020)
This study aims to find out how the changes made by academic librarians in the era of disruption so that the profession of librarians is not extinct. The type of method used in this research is qualitative research with a descriptive approach. This research involved five librarians from several private university libraries in Bandung as key informants. The selection of informants was carried out using a purposive sampling technique with the intention that the selected informants according to certain criteria were relevant to the context of the problem in this study. The results showed that as a profession, librarians cannot work alone, meaning librarians need to collaborate with anyone such as lecturers, researchers, students, and the community. Examples of collaboration that can be done such as making software and doing various activities. Academic librarians in the era of disruption are also required to be willing to learn to be ready to follow all changes and adapt to the environment. Academic librarians must also continually update their knowledge and insights about research trends so that librarians can assist users in conducting scientific research and publications. The conclusion from this study shows that there are several efforts that can be done by librarians so that the librarian profession does not become extinct, namely collaborating, learning, and helping users.